Legal Validity of Power of Attorney to Sell in Non-Performing Loans - Muhammad Ramadhan Zulfikar Mahendra; Imam Kuswahyono; Djumikasih (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2026)
This study examines the use of a Power of Attorney to Sell (Surat Kuasa Menjual/SKM) as a substitute for Mortgage Rights (Hak Tanggungan) in the settlement of non-performing loans through the Simple Lawsuit (Gugatan Sederhana/GS) mechanism. The issue arises because Supreme Court Regulation Number 4 of 2019 restricts the resolution of land rights disputes through the GS mechanism, while in practice, loan disputes secured by land rights are still being resolved through GS using an SKM. This research aims to analyze the legal position of the GS mechanism in loan disputes involving land rights as collateral and to assess the legal validity of using an SKM as a substitute for Mortgage Rights. This study employs normative legal research using statutory and conceptual approaches. Primary, secondary, and tertiary legal materials were analyzed qualitatively through grammatical, systematic, and teleological interpretation methods. The analysis is grounded in Gustav Radbruch’s Theory of Legal Certainty, Sri Soedewi Masjchoen Sofwan’s Contract Theory, and the doctrine of legal circumvention (fraus legis). The findings indicate that the use of the GS mechanism in loan disputes secured by land rights is inherently connected to land rights disputes; therefore, its application must be strictly limited in accordance with Supreme Court Regulation Number 4 of 2019. Furthermore, an SKM cannot be equated with Mortgage Rights because it does not fulfill the principles of publicity and specificity as required under the Mortgage Rights Law. Accordingly, clearer limitations regarding land rights disputes within the GS mechanism and stronger regulations governing the use of SKM are necessary to ensure legal certainty and the protection of land rights.